Analysis Of Identity Confusion And Mistaken Identities In The Comedy Of Errors - Ammar Muhammad Ra'id Zhafir Nur Haqiki Riyadi (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This academic study explores the issue of identity uncertainty and mistaken identities in William Shakespeare's well-known farce, "The Comedy of Errors," critically. The story, which centers on two pairs of identical twins who were split up at birth, presents a number of humorous and confusing situations that are sparked by misidentification. The research explores the relevance of misidentification, the function of irony in these situations, and the interpersonal tensions and relationships among characters through the use of text analysis and a qualitative technique. This research, which is grounded on Erikson's psychological developmental model and incorporates dramatic aspects, demonstrates the enduring influence of Shakespeare's unique language style in illustrating the complex nature of mistaken identity.